(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2012)
The archaeological excavation organized by the University of Milan in the site of Gortys (Crete) between 2009 and 2010 on the northern side of the Terme Milano, revealed a big rectangular room, explainable as an apodyterium. The room, characterized by a re-used stone slabs paving, bounds the northern side of the complex and testifies the II phase of life of the building and the following phase of abandonment, prior to the spreading of the bizantin quarter.